TRANSPORT AND COHESION POLICY IN THE CZECH REPUBLIC IN THE PERIOD 2007-2013 (Perner's Contacts, 2010)
Transport may be considered to be a cornerstone of current society. Transport infrastructure investments and sustainable transport belong to the most often discussed transport themes and issues. And just on these two themes EU cohesion policy is oriented in the Czech Republic, with a decisive role of Operational Programme Transport and regional operational programmes in the structure of Czech operational programmes. Therefore, approved transport projects of OP Transport and ROP Central Moravia are analyzed in the article. The main findings point at the preference of new transport infrastructure construction to the development of sustainable urban transport systems. Spatially, there are disparities between core and peripheral regions of the Czech Republic when the decisive share of funds is allocated close to the main development centres. However, also peripheral regions have specific opportunities, based on their endogenous development strengths, to benefit from cohesion policy.
Keywords: transport; cohesion policy; OP Transport; ROP Central Moravia